Владыки Мегамира: [фантастический роман] / Ю. А. Никитин - Никитин Юрий Александрович (Мегамир, 2002)
Экземпляры: ф.8 (ретро) / Инвентарный номер: 36879 / Цена: / Сис.шифр: 84(2Рос)6 / Авт.знак: Н 62 / ББК: 84(2Рос=Рус)6